2019
DOI: 10.1115/1.4041150
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Analysis of a NACA 0021 Airfoil Section at Low Reynolds Numbers Based on Experiments and Computational Fluid Dynamics

Abstract: The wind industry needs airfoil data for ranges of angle of attack (AoA) much wider than those of aviation applications, since large portions of the blades may operate in stalled conditions for a significant part of their lives. Vertical axis wind turbines (VAWTs) are even more affected by this need, since data sets across the full incidence range of 180 deg are necessary for a correct performance prediction at different tip-speed ratios. However, the relevant technical literature lacks data in deep and postst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In order to assess the effectiveness of the numerical techniques prior to proceed with the extended sensitivity analysis on the GF effects on the airfoil in Darrieus-like motion, an experimental benchmark was identified. In particular, the test case presented by researchers from the Technical University (TU) of Berlin in [16] was used. Dedicated experimental studies were conducted inside the laminar wind tunnel of the Hermann Föttinger Institute.…”
Section: Experimental Validation Benchmarkmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to assess the effectiveness of the numerical techniques prior to proceed with the extended sensitivity analysis on the GF effects on the airfoil in Darrieus-like motion, an experimental benchmark was identified. In particular, the test case presented by researchers from the Technical University (TU) of Berlin in [16] was used. Dedicated experimental studies were conducted inside the laminar wind tunnel of the Hermann Föttinger Institute.…”
Section: Experimental Validation Benchmarkmentioning
confidence: 99%
“…The choice of the bullet-shaped domain was due to the possibility of imposing only an inlet (at which values of the velocity vector, turbulence intensity, and turbulent viscosity ratio were assumed) and an outlet boundary (at which the value of the gauge pressure was assumed, and for all other quantities zero normal derivative was assumed), with benefits in terms of calculation stability. The same approach was followed successfully in [16]. The works by Balduzzi et al [20] were taken as the main references in order to select the most suitable numerical settings for the solver.…”
Section: Numerical Cfd Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A full description of dynamic stall would be extraneous here but excellent reviews can be found in McAlister et al (1978), McCroskey (1982), McCroskey (1981, Leishman (2002) and Carr (1987). More modern experimental works can be found in Granlund et al (2014), Mulleners and Raffel (2013), , ), Müller-Vahl et al (2017, Strangfeld et al (2015), Balduzzi et al (2019), and Holst et al (2019). For the discussion here, it is sufficient to note that as the strength and phase of the leading vortex varies, so will the aeroelastic stability.…”
Section: Introductionmentioning
confidence: 99%
“…The vortex then travels downstream causing a spike in low pressure across the airfoil which presents as a strong spike in lift and a strong dump in the moment. A full description of dynamic stall would be extraneous here but excellent reviews can be found in McAlister et al (1978); McCroskey (1982McCroskey ( , 1981; Leishman (2002); Carr (1987) and more modern experimental works can be found in Granlund et al (2014); Mulleners and Raffel (2013); ; ; Muller-Vahl et al (2017); Müller-Vahl et al (2015); Stangfeld et al (2015); Balduzzi et al (2019); Holst et al (2019)). For the discussion here, it is sufficient to note that the strength and phase of the leading vortex varies, so will the aeroelastic stability.…”
mentioning
confidence: 99%